Phosphatidic acid formation is required for extracellular ATP-mediated nitric oxide production in suspension-cultured tomato cells - Sueldo, Daniela J (The New phytologist, 2010)
*In animals and plants, extracellular ATP exerts its effects by regulating the second messengers Ca(2+), nitric oxide (NO) and reactive oxygen species (ROS). In animals, phospholipid-derived molecules, such as diacylglycerol, phosphatidic acid (PA) and inositol phosphates, have been associated with the extracellular ATP signaling pathway. The involvement of phospholipids in extracellular ATP signaling in plants, as it is established in animals, is unknown. *In vivo phospholipid signaling upon extracellular ATP treatment was studied in (32)P(i)-labeled suspension-cultured tomato (Solanum lycopersicum) cells. *Here, we report that, in suspension-cultured tomato cells, extracellular ATP induces the formation of the signaling lipid phosphatidic acid. Exogenous ATP at doses of 0.1 and 1 mM induce the formation of phosphatidic acid within minutes. Studies on the enzymatic sources of phosphatidic acid revealed the participation of both phospholipase D and C in concerted action with diacylglycerol kinase. *Our results suggest that extracellular ATP-mediated nitric oxide production is downstream of phospholipase C/diacylglycerol kinase activation